Gingival Involvement in IgG4-Related Disease - Sarah Al Qassimi; Rajaie Namas; Ahmed Alduaij; Anastasios Hantzakos; Mahdi Shkoukani (European Journal of Rheumatology, 2025)
Cite this article as: Al Qassimi S, Namas R, Alduaij A, Hantzakos A, Shkoukani M. Gingival involvement in IgG4-related disease. Eur J Rheumatol. 2025, 12(3), 0023, doi:10.5152/eurjrheum.2025.25023.